Incorporation of Capecitabine Into Extended Chain of N-Acylated Chitosan Carrier - Anita Marlina; Misni Misran; Witta Kartika Restu (Advances in Polymer Technology)
Enhancing the hydrophobicity of chitosan through acylation enables the encapsulation of water-insoluble drugs within the polymeric carrier cores. In this study, hydrophobically modified chitosan was synthesized by reacting low-molecular-weight chitosan with acyl chloride (C18–C24) using an agitation method under mild conditions. The structure of acylated chitosan was analyzed using FTIR and 1H-NMR spectroscopy. The degree of substitution (DS) varied between 56% and 69% for different long-chain N-acylated chitosan, with N-stearoyl chitosan (ChC18) exhibiting the highest DS. The incorporation of capecitabine (CAP) into extended acylated chitosan increased particle size and decreased zeta potential. N-lignoceroyl chitosan (ChC24) exhibited the highest zeta potential value of −27 mV for 0.2 mg of CAP, indicating that the most extended acyl group was the most stable in the suspension. Transmission electron microscope images revealed that all acylated chitosan particles were spherical, with sizes ranging from 100 to 200 nm, and existed as stand-alone entities, indicating excellent stability in suspension. The loading of CAP increased in particle size but did not alter particle shape, except for ChC24, which exhibited agglomeration. SEM images revealed that the individual arrangement of particles in CAP-ChC18 made it more stable than other acylated chitosan. In contrast, the formation of clusters in CAP-ChC24 can be attributed to strong hydrophobic interactions. X-ray photoelectron spectroscopy results show that there is no nitrogen atom in ChC18, which means that the acyl group is oriented inward and bound to the stearoyl group via van der Waals forces. At different drug weight-to-carrier ratios, the encapsulation efficiency (EE) of CAP with varying acyl group lengths ranged from 85% to 97%. The drug loading (DL) capacity and EE increased as the amount of drug in the carrier increased. However, the length of the acyl group did not significantly affect DL and EE, even when the carrier-to-drug ratio was consistently maintained. Sustained release was observed in CAP-loaded ChC24, indicating a significant influence of the extended chain on chitosan. Consequently, extended N-acylated chitosan possesses enormous potential as a drug delivery system for CAP.